The Relationship Between Leadership Functions, Business Analytics, and Business Continuity in Economic Development Unit in Sharjah, United Arab Emirates (UAE) - Almheiri, Khalifa Mohamed Obaid Bitterish (2024)
The primary purpose of this study was to investigate the effect of leadership functions (challenging the process, inspiring a shared vision, enabling others to act, modelling the way, and encouraging the heart) on business continuity among public organizations in the UAE. The study also examined the moderating effect of business analytics on the relationship. This study considers two main theories that are used in explaining the relationships that exist between leadership functions, business analytics, and business continuity. The theories are Exemplary Leadership and Resource-Based View (RBV) theories. Questionnaires were distributed to 357 employees working in the economic development unit in Sharjah, UAE. 265 questionnaires were returned, but only 254 were used in the analysis using Structural Equation Modelling (SEM) - Partial Least (PLS) method. The results of the study revealed a significant effect of challenging the process, inspiring a shared vision, enabling others to act, modelling the way, and encouraging the heart on business continuity. The study also revealed that the moderating role of business analytics was significant in the effect of challenging the process, inspiring a shared vision, enabling others to act, modelling the way, and encouraging the heart on business continuity. The present study also highlighted the implications of the research, future research recommendations as well as its limitations.